To study the role of migratory farm labour in agricultural production in Sind province of Pakistan - Siddiqi, Sharif Ahmed (Dept. of Agricultural Economics & Rural Sociology, Sind Agricultural University, 1978)
Report covers the period from Feb. 1, 1977 to Jan 31, 1978.